Effect of binary builder on properties of fish jellies - Victotia V. Krashchenko; Yulia V. Karpenko (Известия ТИНРО)
Effect of binary gelatin-chitosan builder on properties of fish jellies is investigated. The model jellies were prepared of the pacific grenadier Allbatrosia pectoralis with the meat distinguished by high water content. Acid-soluble chitosan with molecular weight 588 kd (made by Biopolimery) and water-soluble chitosan with molecular weight 40 kd (made by Bioprogress) were used for the structure builder in combination with gelatin. After adding the binary builder into the fish jelly, the gelatin increases its strength and the chitosan enhances its functional-technological and rheological properties; organoleptic properties of the finished product are also good: it has pleasing fishy taste and aroma. Moreover, the adding of chitosan lowers water activity. Rate of the lowering depends both on type of chitosan and on its concentration. The acid-soluble chitosan lowers the index of water activity Aw by 4.5-15.7 %, and the water-soluble chitosan - by 3.2-13.3 %. The maximal lowering of water activity is observed under the chitosan concentration (in solids) 0.08 g per100 g of jelly, for both types of chitosan. The jelly samples with this content of chitosan have the best organoleptic properties, too. The chitosan concentration increasing over 0.32 g/100 g causes an increase of the index Aw. The effect of water activity lowering is explained by forming of polyelectrolytic complex in the system jelly-chitosan-gelatin that fixes free water. The acid-soluble chitosan is more effective for water activity lowering than the water-soluble chitosan.